EXAMEN ESPECIAL A LAS CUENTAS DE BANCOS Y MANTENIMIENTO DE VEHÍCULOS DEL CUERPO DE BOMBEROS DE LA CIUDAD DE LOJA EN EL PERIODO 2013 - Ruíz Astudillo, Karla daniela (2015)
The thesis called, " SPECIAL EXAMINATION TO THE ACCOUNTS OF BANKS AND MAINTENANCE OF VEHICLES OF THE FIRE BRIGADE OF LOJA's CITY IN THE PERIOD 2013 " has been developed on the basis of arranged in the Regulation of Academic Regime of Loja's National University, as prerequisite when Auditor chose the Engineer's title in Accounting and Audit Public Book-keeper-; the same one that was executed to offer a contribution to the executives of this institution for the suitable and opportune capture of decisions, on the other hand is necessary to indicate that it has been achieved to expire with the general aim raised since to be to realize a Special Examination to the accounts of Banks and Maintenance of Vehicles of this public entity, for which was necessary to develop the following specific aims. The first specific objective is: "To evaluate the internal control system implemented by the institution in the period 2013" the same as I run applying the Internal Control Standards and laws and regulations subject to the Public Sector through Control Questionnaire Internal order to determine the level of trust and risk in handling accounts in studio. The second specific objective is: "Check the fairness and reliability of the balances of the accounts of banks and maintenance of vehicles of the Fire Department of the City of Loja in the period 2013 to present the company to see if they have been used efficiently "we proceeded to analyze the 6 area being examined and described by the help of the narrative and the respective working papers bonds that allowed evaluate the safety and authenticity of transactions that managers and administrative manage the financial resources of the institution. The third specific objective was "To present the Report of the Special Review the Administrative Director of the Fire Department of the City of Loja containing comments, conclusions and recommendations to help improve financial services", which record the audit report of it is left results of the special examination. The methodology allowed to fully achieve compliance with the above objectives was taken as reference to Government Financial Audit Manual and thus to proceed to implement the phases of the Special Examination. In the first phase: Planning the Special Examination occurs where preliminary planning was performed in which the recognition of the institution and its main activities are fulfilled, then the Planning Specifies through Assessment Internal Control System Component ; in the second phase of field work where the procedures in the audit program by component is fully applied and developed significant findings properly evidenced and supported in working papers where sufficient evidence is concrete and develops competent and supports the view that the report also narratives bonds, and summary bonds were used; The third phase is the communication of results and culminates with the presentation of the final report, containing the same letter, comments, conclusions, and recommendations. 7 Finally and most important conclusion we can state that the internal control system that maintains the institution has some shortcomings that must be corrected, the same as detailed in the respective report of the Special Review, noting that in the Division of Administration, Bonds and cash reconciliations independently of the registration of bank transactions are made, presenting a low risk level and a high level of confidence with a percentage of 97.3% for bank accounts, in this situation the institution shall organize organize better the people working in this division assigning roles or providing written an independent person to record transactions mentioned Division to perform the verification of bank reconciliations in a timely manner so that it complies effectively with their activity, since the leads to accumulation of functions fall into involuntary human errors which can not generate a reasonable information for timely decisions related to liquidity; and also for the maintenance of vehicles has seen presents a low risk level and a high level of confidence with a percentage of 96.875% by virtue of this result so frequent monitoring of vehicles that they have the loan documentation was available and that it is within reach and view of those working under their responsibility in order to have an accurate knowledge in order to demonstrate compliance with the provisions legales and custody of the vehicles of the institution.